Electrical power transmission system engineering : analysis and design - Gonen, Turan (Boca Raton : Taylor & Francis, 2014)
'A hands-on electrical and mechanical design text for engineering students and practicing professionals, Electrical Power Transmission System Engineering: Analysis and Design, Third Edition features additional examples of fault analysis, a detailed discussion of flexible alternating current transmission systems, and expanded coverage of the structures, equipment, and environmental impact of transmission lines. The author clearly and carefully explains basic material to build a solid foundation of the fundamentals before tackling key topics including transmission system planning, supervisory control and data acquisition, the use of static compensation to prevent voltage collapse or instability, overhead power transmission line modeling and construction, sag and tension analysis, underground power transmission and gas insulated transmission lines, direct current power transmission, transient overvoltages, limiting factors for extra-high and ultra-high voltage transmission, symmetrical components, transmission system protection, reliability, and more'--
Includes bibliographical references and index.
Keywords: Electric power transmission